Layered inoculation of anaerobic digestion and anammox granular sludges for fast start-up of an anammox reactor - Liu, Yanxu; Liu, Wen; Li, Yu-You; Liu, Jianyong (Bioresource Technology, 2021)
[Display omitted] •Layered inoculation of anammox & AD granular sludges was proposed to start anammox.•Layered inoculation reduced cell lysis and lag phases to 1 day.•Nitrogen loading rate reached 11 kg N/m3 d in 42 days by layered inoculation.•Adsorption, interception and domestication enhanced anammox activity of AD sludge. Layered inoculation of anaerobic digestion (AD) and anammox granular sludges was performed for fast start-up of anammox using an expanded granular sludge bed (EGSB) reactor (R1) with the cell lysis phase and the lag phase being shortened. The maximum nitrogen loading rate (NLR) and nitrogen removal rate (NRR) of R1 were 11 kg N/m3 d and 9.9 kg N/m3 d on day 42, respectively. The domesticated AD granular sludge on the upper layer was collected to another EGSB reactor (R2) to investigate its anammox activity. The results showed that AD granular sludge in R1 had anammox activity and could be cultured into anammox granular sludge. Adsorption, interception and domestication enhanced the biomass of anammox bacteria in R1, accelerating the start-up of the reactor. The findings of this work were expected to solve the problem of fast start-up of an anammox reactor with insufficient anammox seeding sludge in industrial application.